ECONOMIC SECURITY OF TECHNICAL UNIVERSITY: THE ANALYSIS OF DYNAMICS OF INDICATORS ON THE EXAMPLE OF NSTU N.A. R.E. ALEKSEEV - Sergey M. Dmitriev; Mikhail V. Shiriaev; Sergey N. Mityakov (Высшее образование в России)
The article finishes a cycle of publications by the title «Economic security of the technical university». The dynamics of indicators of economic security of Nizhny Novgorod State Technical University n.a. R.E. Alekseev is analyzed. Possibility of the joint analysis of rated indicators with the use of petal charts is shown. The detailed analysis of dynamics of change of indicators in various projections of system of economic security of the technical university, the comparative analysis of dynamics of the generalized indexes for various projections and the analysis of dynamics of the generalized index of economic security of the university are carried out. The results of the analysis showed the positive tendencies of development of system of economic security of NSTU.